Daya saing dan dampak kebijakan pemerintah terhadap komoditas jagung hibrida unggul Madura - Mokh. Rum; Novi Diana Badrut Tamami; Sri Ratna Triyasari (University of Islam Malang, 2020)
This study aims to determine the competitiveness and impact of government policies on Unggul Madura Hybrid Maize. The location of the research of corn farming in two villages, namely Duko Tambin and Banyubeseh, Tragah District, Bangkalan, Madura. Determination of the study's location was carried out deliberately (purposive) with consideration in both villages in the development of Unggul Madura Hybrid Maize varieties. The analysis method uses the PAM (Policy Analysis Matrix) matrix. The analysis results show that Unggul Madura Hybrid Maize has quite high competitiveness, which has competitive and comparative advantages. Government policy has a significant impact on Unggul Madura Hybrid Maize farming income, especially on private profits.